The event that provoked the outbreak of the so-called «Revuelta del Arrabal» according to the Muqtabis II from Ibn Hayyān Some remarks about the meaning of the passage - Ruiz Girela, Francisco (Anaquel de Estudios Árabes, 2005)
A close reading of the text Muqtabis II from Ibn ayyān that deals with the event that provoked the outbreak of the so-called «Revuelta del Arrabal» («The Revolt of the Suburb» [of Córdoba]) offers new possibilities to interpret the passage in such a way that a more coherent and stimulating approach to how this event started can be given.